2021
DOI: 10.1093/hmg/ddab060
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants with fetal effects on birth weight are enriched for proximity to genes implicated in rare developmental disorders

Abstract: Birth weight is an important factor in newborn survival; both low and high birth weights are associated with adverse later-life health outcomes. Genome-wide association studies (GWAS) have identified 190 loci associated with maternal or fetal effects on birth weight. Knowledge of underlying causal genes is crucial to understand how these loci influence birth weight, and links between infant and adult morbidity. Numerous monogenic developmental syndromes are associated with birth weights at the extreme ends of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…We were interested in exploring whether there was an enrichment of DDG2P genes in EA GWAS loci. We hypothesized that the EA-PGS could include single-nucleotide polymorphisms (SNPs) in cis -regulatory regions of monogenic DDG2P genes; therefore, we examined the proximity between the 599 autosomal dominant DDG2P genes and 3,952 SNPs included in the EA-PGS, using simulations of matched SNPs (10,000 lists of matched SNPs per GWAS SNP, based on allele frequency and proximity to genes) to empirically test whether the genes fall disproportionately close to the GWAS loci 42 . As expected, we found that the GWAS loci were closer to DDG2P genes than expected by chance alone ( P = 0.005), suggesting that the large-effect rare variants and small-effect common variants may work through overlapping biological pathways.…”
Section: Resultsmentioning
confidence: 99%
“…We were interested in exploring whether there was an enrichment of DDG2P genes in EA GWAS loci. We hypothesized that the EA-PGS could include single-nucleotide polymorphisms (SNPs) in cis -regulatory regions of monogenic DDG2P genes; therefore, we examined the proximity between the 599 autosomal dominant DDG2P genes and 3,952 SNPs included in the EA-PGS, using simulations of matched SNPs (10,000 lists of matched SNPs per GWAS SNP, based on allele frequency and proximity to genes) to empirically test whether the genes fall disproportionately close to the GWAS loci 42 . As expected, we found that the GWAS loci were closer to DDG2P genes than expected by chance alone ( P = 0.005), suggesting that the large-effect rare variants and small-effect common variants may work through overlapping biological pathways.…”
Section: Resultsmentioning
confidence: 99%